Oral Administration of N-Acetyl-seryl-aspartyl-lysyl-proline Ameliorates Kidney Disease in Both Type 1 and Type 2 Diabetic Mice via a Therapeutic Regimen. (20th March 2016) - Nitta, Kyoko; Shi, Sen; Nagai, Takako; Kanasaki, Megumi; Kitada, Munehiro; Srivastava, Swayam Prakash; Haneda, Masakazu; Kanasaki, Keizo; Koya, Daisuke
Abstract : Kidney fibrosis is the final common pathway of progressive kidney diseases including diabetic nephropathy. Here, we report that the endogenous antifibrotic peptide N-acetyl-seryl-aspartyl-lysyl-proline (AcSDKP), the substrate of angiotensin-converting enzyme (ACE), is an orally available peptide drug used to cure kidney fibrosis in diabetic mice. We utilized two mouse models of diabetic nephropathy, streptozotocin- (STZ-) induced type 1 diabetic CD-1 mice and type 2 diabetic nephropathy model db/db mice. Intervention with the ACE inhibitor imidapril, oral AcSDKP, or imidapril + oral AcSDKP combination therapy increased urine AcSDKP levels. AcSDKP levels were significantly higher in the combination group compared to those of the other groups. AcSDKP oral administration, either AcSDKP alone or in addition to imidapril, ameliorated glomerulosclerosis and tubulointerstitial fibrosis. Plasma cystatin C levels were higher in both models, at euthanasia, and were restored by all the treatment groups. The levels of antifibrotic miRs, such as miR-29 or let-7, were suppressed in the kidneys of both models; all treatments, especially the combination of imidapril + oral AcSDKP, restored the antifibrotic miR levels to a normal value or even higher. AcSDKP may be an oral antifibrotic peptide drug that would be relevant to combating fibroproliferative kidney diseases such as diabetic nephropathy.